Does coping style mediate the relationship between knowledge and psychosocial outcomes in women with atrial fibrillation? - Le Grande, Michael R.; Salvacion, Marielle; Shwaita, Lubab; Murphy, Barbara M.; Jackson, Alun C.; Alvarenga, Marlies E. (Frontiers in Psychiatry, 2024)
Introduction: In patients affected by atrial fibrillation (AF) disease-specific knowledge and coping style may be associated with psychosocial well-being. This study aimed to determine if coping style (problem-focused, emotion-focused, avoidance-focused) mediated the relationship between patient knowledge and three psychosocial outcomes (anxiety, depression and life satisfaction). Methods: In 2021 a total of 188 women with reported AF, and ages ranging from 18 to 83 years (mean 48.7, sd 15.5 years), completed an online questionnaire consisting of sociodemographic, clinical and AF knowledge questions and psychosocial instruments (Anxiety and depression, the Hospital Anxiety and Depression (HADS) scale; life satisfaction, Satisfaction With Life Scale (SWLS); and coping style (Brief COPE). Using Jamovi statistical software three individual mediational models (for anxiety, depression and life satisfaction) were constructed assessing the direct and indirect relationships between knowledge, coping style and each psychosocial outcome. Age was a covariate in each model. Results: The mediation analyses demonstrated significant direct negative associations between AF knowledge and HADS anxiety and depression and positive associations with SWLS. There were also direct associations between each of the three coping styles and the three psychosocial outcomes. There were significant indirect effects of coping style between AF knowledge and each of the three outcomes confirming partial mediation effects. Discussion: These findings highlight the crucial role of coping style in mediating the association between AF knowledge and psychosocial outcomes. As such, interventions aimed at increasing patient knowledge of AF may be more effective if adaptive problem-solving coping strategies are also demonstrated to these patients. Additionally, modification of maladaptive coping strategies as part of the psychological management of patients with AF is highly recommended.